Strength Evaluation of Reinforced Concrete Structure for Regular Building due to Earthquake Load Based on Different Soil Types - Jonie Tanijaya (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
Earthquakes are natural events caused by tectonic plate movements and it is unpredictable. Thus, the building design regulation has an important role in ensuring the Earthquake resistant structure. A commonly used method is the response spectrum method. For different soil types, the value of the design spectra may increase or decrease. Therefore this study aims to determine the effect of soil type on the strength of reinforced concrete structures, especially the building behavior and structural internal forces. Analysis results show that the increase of base-shear value of Makassar is about 34% and 103% for medium soil and soft soil condition compared to hard soil. The increase of beam negative moment is about 27% to 39% in soft soil compared to hard soil, while the value is about 8% to 14% in medium soil compared to hard soil. The increase of beam positive moment varies considerably between 8% to 50%. The increasing moment is directly proportional to the required reinforcement area of the beam. Demand capacity ratio of column has also increased about 10% to 35% for medium soil and soft soil compared to hard soil.